Pengaruh Konsentrasi HCl Pada Proses Exfoliasi Graphene Oxide/Reduce Graphene Oxide (GO/rGO) Dari Karbon Bulu Ayam - Erna Hastuti; Feny Fefiyanti; Muthmainnah muthmainnah (Department of Physics, Sebelas Maret University, 2022)
An increase in the consumption of chicken meat may have an impact on the waste of chicken feathers. Several efforts have been made to treat chicken feather waste, which is difficult to decompose and can pollute the environment. Chicken feathers are biomass with a high keratin content that has the potential to be used as a carbon material. In this study, chicken feathers were used in the chemical exfoliation method to produce reduced Graphene Oxide (rGO) material. Chicken feathers are heated in two stages, at temperatures of 250 and 400 ℃ in the air. The exfoliation procedure was carried out with varying concentrations of HCl (0, 0.5, 1, 1.5, and 2 M). The X-ray diffraction spectra revealed that the sample had a rGO type carbon phase, with the crystal size decreasing as the HCl concentration increased. The presence of functional groups C-O, C=C, and C-OH identified as GO/rGO was revealed by FTIR spectra. The HCl exfoliation process reduced the sample's conductivity and capacitance, with the highest values obtained in aquadest sample (GO-0 M), about 10-5 S/m and 10-7 F/m2.